Характеристика преимагинальных фаз и экология лохмеи боярышниковой (Lochmaea crataegi Forst.) - Бровдий, В.М. (Вестник зоологии, 1971)
Lochmaea crataegi F о г s t. is distributed all over the right-bank Ukraine. It propagates in quantity on Prunus spinosa L. bushes, more rarely — on Crataegus L. The life cycle of the pest is univoltine and lasts for 53—57 days. The beetles affect buds, pedicels, flower ovaries and leaves, the larvae — fruit of these plants. The female lays 80—130 eggs. In places of mass propagation L. crataegi Forst . can also inhabit Malus M i l l and affect its flowers, leaves and fruit. The characteristic of an egg, larva and pupa is given. The peculiarities of L. crataegi Forst . ecology under conditions of the Ukraine are presented.